Examining the Therapeutic Alliance: A Case Study At a Drug Rehabilitation Facility - Isa Amat, Mohamad; Mohd Sukor, Nurhafizah; Suhaila Ku Johari, Ku; Mohd Najib, Nurfarhah (International Journal of Psychosocial Rehabilitation, 2020)
An enhanced understanding of therapeutic alliance in drug treatment settings as a peer support community facilitates recovering counselors (RC) and clients in the passage of recovery. The current study explored the therapeutic alliance between recovering counselors (RC) and their clients in a non-governmental drug treatment and rehabilitation center. It aims to explore the therapeutic alliance of recovering counselors—client relationships and interaction that influence the recovering journey. In this study, recovering counselor (RC) refers to experienced and qualified counselors who have completed a Therapeutic Community (TC) program. An in-depth case study was conducted involving 3 pairs of counselors and clients who volunteered to participate in the study. The data were collected through 16 in–depth interview sessions, observations, and personal reflections. The qualitative data suggest that the experience of therapeutic alliance was represented by three major themes: 1) therapeutic relationship, 2) spirituality, and 3) successful recovery and behavior change. Each pair of counselors-clients reflects a different level of therapeutic experience as the clients make progress from primary treatment to re-entry phases. The findings help to enhance the knowledge on how a therapeutic alliance helps both counselors and clients to flourish as progressive individuals. This study suggested that recovering counselors become a role model for clients to sustain their recovery and motivation for behavior change. However, further investigations are needed to support the current findings. Implications for future study are also discussed.